Efectos del tiempo de fermentación y las variedades de yuca sobre la calidad fisicoquímica y microbiológica del almidón - Murillo Loor, Raúl Clemente (2022)
The objective of this research was to determine the cassava variety and the fermentation time that improve the expansion capacity of the native starch, the effect of the fermentation time variables (10, 18 and 25 days) and the cassava varieties (INIAP PORTOVIEJO 650, 651 and 652). The medium fermentation of the process was enriched by adding glucose syrup (0.5%) and yeast extract (0.2%) to all treatments and sun drying was applied. The physicochemical quality was evaluated, through analysis of pH, titratable acidity, humidity, ashes of the raw materials and the best treatment corresponding to the variety of cassava INIAP PORTOVIEJO 652, which also determined the expansion capacity. The microbiological quality of the best treatment was analyzed by means of count analysis of total coliforms, E. coli, molds and yeasts. A statistical design was applied with a factorial arrangement analyzed by means of a DCA. The results indicate that when evaluating the expansion capacity of the starches, there were statistical differences in relation to the fermentation time and the varieties of cassava, as well as the interactions between these two factors. The starch of variety 652 reached, on average, the highest expansion power after 18 days of fermentation, reaching 14.83 cm3 / g, with microbiological levels permissible for human consumption. The starch obtained due to its high baking powder becomes an important functional raw material for uses in baking and things alike.